Eine Elfenbeinpyxis in Wien mit Krippenaltar und ein allegorischer Esel - Warland, Rainer 1951- (Jahrbuch für Antike und Christentum, 2023)
The ivory pyxis in the Kunsthistorisches Museum in Vienna showing narratives of the Nativity of Christ, which is attributed partly to the 6th century and partly to the 9th century, combines two scenes of completely different natures. The first is a hieratic-frontal Nativity scene with oversized representations of the allegorical animals ox and donkey, the second, in contrast, an impetuously moving narrative group of approaching magi arriving with lavish gifts. The allegorical Nativity scene in particular, with its brick-built manger, separately seated Mary to one side and the child gazing up to heaven, has its roots in the pictorial compositions of the Justinianic ivory cathedra in Ravenna (around 546), producing a liturgical remodelling of the manger as a Nativity altar in depictions of the early Middle Ages.